Impact of discounts on sales in Delhi NCR: a survey report - Meena, Rohit; Kumar, Ashwini (International Journal of Scientific Reports, 2024)
Background: Delhi NCR, which includes Delhi and its neighbouring areas, has experienced considerable growth in the shopping sector over the past decade. A major factor that draws customers to these shopping destinations is the opportunity for bargaining and discounts. This paper examines the impact of discounts on the sales of various item categories. Methods: A survey has been conducted to collect data. Along with focus on responses to a structured questionnaire, the study also analyses sales across various groups of items, with each group divided into two categories: one offering discounts and the other not. Results: findings of this study have the potential to shed light on the fact that offering discounts is beneficial and finally leads to increase in sales as it attracts more customers. For most the groups an increase in sales has been witnessed. Conclusions: From the findings of the study, it can be concluded that if discounts are offered, more customers are attracted which eventually leads to increase in sales day by day.